Pleading Patent Infringement: Applying the Standard Established by Twombly and Iqbal to the Patent Context - Steinmetz, Adam (Science and Technology Law Review, 2012)
Recent landmark Supreme Court decisions established plausibility as the new pleading standard in a civil lawsuit. However, it is not always clear how the facts of an individual case fit into such a standard, particularly in patent infringement litigation. This Note seeks to address this question by conducting a detailed investigation of the pleading requirements in recent patent infringement cases. First, the Note investigates whether a patent holder must specify the means by which the defendant allegedly infringes at the pleading stage: whether the complaint must identify alleged infringing devices, and whether it must also put forth a theory of infringement. Second, the Note investigates Form 18—an example of a sufficiently pled patent complaint that has not been updated in the Federal Rules since the recent Iqbal and Twombly cases, and finds that judges have used a number of approaches to reconcile Form 18 with the new pleading standard. Third, the Note discusses what should be the applicable precedent for evaluating pleading issues in patent cases. Since procedural issues and substantive patent law issues may become intertwined under a plausibility standard, patent pleading issues should be controlled by the Federal Circuit, rather than the regional circuit courts. Finally, the Note proposes a common line of inquiry that courts should take in resolving patent infringement pleading issues. In ruling on a FRCP 12(b)(6) motion to dismiss, the court should ask whether the plaintiff’s complaint has guided the course of discovery on the issue. If it has not, the motion to dismiss should be granted.